Timing and tectonic setting of Ordovician volcanic rocks of the Miramichi terrane in eastern Maine, USA, and southwestern New Brunswick, Canada - Ludman, Allan; Whittaker, Amber; O'Sullivan, Paul; McFarlane, Christopher (Atlantic Geoscience, 2025)
New U-Pb LA-ICP-MS ages and geochemical data from volcanic rocks in the southwestern part of the Miramichi terrane in Maine, USA, and the Eel River area, New Brunswick, Canada, indicate that calc-alkaline continental arc volcanism began in the earliest Ordovician (ca. 480 Ma) and continued into the Middle Ordovician (at least as late as ca. 463 Ma). The overlap of volcanic rock ages from the Greenfield (ca. 478–463 Ma) and Danforth, Maine (ca. 467–475 Ma), and Eel River, New Brunswick (ca. 480–468 Ma), segments of the terrane confirm previously uncertain correlations of the Olamon Stream (Greenfield), Stetson Mountain (Danforth), and Porten Road and Eel River (Eel River) formations in these areas. The youngest Middle Ordovician ages overlap those of the oldest units of the Tetagouche Group in northern New Brunswick which are attributed to crustal extension leading to opening of the Tetagouche back-arc basin.Silicic and mafic Tetagouche Group rocks plot in within-plate fields on tectonic discrimination diagrams, distinctly different from the volcanic arc fields for the coeval silicic and mafic rocks in the two Maine segments and the Eel River segment in New Brunswick. Continental arc volcanism in the southwestern Miramichi terrane did not cease when arc extension/rifting leading to formation of the Tetagouche back-arc basin began at ca 470 Ma in New Brunswick, as proposed in a previous model that invoked a single migrating arc. Instead, southwestern Miramichi volcanism had extended from at least ca. 480 to 463 Ma—incompatible with short-lived Meductic-phase arc volcanism (ca. 476–472 Ma) proposed in that model.